FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG DI KECAMATAN PALELEH BARAT KABUPATEN BUOL - Amran B Tiban; Fahrudin Zain Olilingo; Irawati Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Amran B. Tiban. Analysis of Factors Affecting Corn Production in West Paleleh District, Buol Regency. Undergraduate Program in Development Economics, Department of Economics, Faculty of Economics and Business, Universitas Negeri Gorontalo. Supervised by Prof. Dr. Fahrudin Zain Olilingo, S.E., M.Si. (Supervisor I) and Dr. Irawati Abdul, S.E., M.Si. (Supervisor II). Corn production is one of the key agricultural commodities that supports food security and increases farmers' income. This study aims to analyze the effects of land area, seed usage, fertilizer application, labor, and pesticides on corn production in West Paleleh District, Buol Regency. The study employed a quantitative approach using primary data collected through questionnaires administered to 95 corn farmers selected by proportionate random sampling. Data were analyzed using the Cobb–Douglas production function, transformed into its natural logarithmic form, and estimated through multiple linear regression using Stata. The results indicate that fertilizer and labor have a positive and statistically significant effect on corn production. Meanwhile, land area, seed usage, and pesticide application have positive but statistically insignificant effects. Simultaneously, all independent variables significantly affect corn production. The coefficient of determination (R²) of 0.5005 indicates that 50.05% of the variation in corn production can be explained by the variables included in the model, while the remaining 49.95% is explained by other factors outside the scope of this study. These findings suggest that improving the efficiency of fertilizer application and labor utilization is a key strategy for increasing corn production in West Paleleh District.